Promoting students' social behavior in primary education through Success for All lessons. (December 2020) - Veldman, M.A.; Hingstman, M.; Doolaard, S.; Snijders, T.A.B.; Bosker, R.J.
Highlights: The effect of Success for All lessons on students' social behavior was investigated. Social emotional learning strategies are embedded in SfA lessons. No general effect of SfA on social behavior of Grade 1-3 students was found. In Grade 2, SfA decreased antisocial behavior of disadvantaged students. Abstract: Success for All (SfA) is a comprehensive school reform program with a strong emphasis on cooperative learning that aims to improve students' social emotional learning alongside students' cognitive learning. In the present study it was examined whether SfA led to improved students' social behavior in Grade 1–3 of primary education. Peer sociometric data was collected for 974 students aged 6–9. Using multivariate multilevel analysis we found no significant effect of SfA on students' pro- and antisocial behavior over time. However, a significant interaction effect was found showing that antisocial behavior of students from disadvantaged backgrounds decreased in the intervention condition in Grade 2. This is a promising finding given that the SfA program was especially developed for schools serving large numbers of disadvantaged students. Implications of the study are described.